A stimuli-responsive anticancer drug delivery system with inherent antibacterial activities. Issue 11 (15th January 2020) - Dey, Subhasis; Patel, Anjali; Raina, Khyati; Pradhan, Nirmalya; Biswas, Oindrila; Thummer, Rajkumar P.; Manna, Debasis
Abstract : Stimuli-sensitive modular lipids with sulfonium moieties have properties like the formation of stable liposomes, high phase-transition temperature, controlled drug release efficiency, low cytotoxicity against mammalian cells, and antibacterial activities. Abstract : We describe a novel class of stimuli-sensitive sulfonium-based synthetic lipids, which exhibit several favorable biophysical properties of phospholipids. The potent sulfonium-based lipid was successfully disassembled by glutathione to release the encapsulated drug molecules in a controlled manner. The cationic lipid also showed lower cytotoxicity against mammalian cells and displayed moderate antibacterial activities.